2003
DOI: 10.1007/bf03021062
|View full text |Cite
|
Sign up to set email alerts
|

Landiolol, esmolol and propranolol protect from ischemia/reperfusion injury in isolated guinea pig hearts

Abstract: P Pu ur rp po os se e: : Beta blockers are thought to exert beneficial effects on the ischemic heart. The authors examined the effects of landiolol (ONO 1101), a highly selective ß1 antagonist, propranolol, a nonspecific ß blocker, and esmolol, a selective ß1 antagonist, on postischemic contractile recovery. Drugs were given prophylactically.M Me et th ho od ds s: : Ischemia-reperfusion in isolated guinea pig hearts was induced by stopping the perfusion for 45 min and reperfusing for 60 min. Hearts (n = 7 in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…We previously reported that landiolol, a new ultrashort-acting, highly selective β 1 -blocker, had a cardioprotective effect in the ischemic heart when it was administered before ischemia [2]. The present study demonstrated that: (1) landiolol, only at the highest dose used, had a cardioprotective effect in hearts subjected to I/R, (2) landiolol also had a cardioprotective effect in hearts subjected to I/R independent of a reduction in cardiac work, (3) landiolol had a cardioprotective effect only when it was administered just before ischemia, and the cardioprotective effect disappeared after washout, (4) landiolol had a lipid peroxidationreducing effect in hearts subjected to I/R although no dose-dependency was shown, and (5) landiolol suppressed I/R-induced PLB phosphorylation at the Ser 16 residue in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that landiolol, a new ultrashort-acting, highly selective β 1 -blocker, had a cardioprotective effect in the ischemic heart when it was administered before ischemia [2]. The present study demonstrated that: (1) landiolol, only at the highest dose used, had a cardioprotective effect in hearts subjected to I/R, (2) landiolol also had a cardioprotective effect in hearts subjected to I/R independent of a reduction in cardiac work, (3) landiolol had a cardioprotective effect only when it was administered just before ischemia, and the cardioprotective effect disappeared after washout, (4) landiolol had a lipid peroxidationreducing effect in hearts subjected to I/R although no dose-dependency was shown, and (5) landiolol suppressed I/R-induced PLB phosphorylation at the Ser 16 residue in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The perfusate was disk-fi ltered (5 µM bore size) in-line and had the following composition (in mM): 137 Na + , 5 K + , 1. [2]. In the clinical setting, landiolol is injected at a rate of 0.125 mg·kg −1 ·min −1 for the fi rst 1 min and then administered at a rate of 0.04 mg·kg −1 ·min −1 continuously.…”
Section: Langendorff Heart Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated Langendorff and working-heart preparation As previously described, 16,17 male English short-haired guinea pigs (250-300 g) were intraperitoneally injected with 20 mg of ketamine and 1000 U of heparin and, after becoming unresponsive to noxious stimulation, were decapitated. After thoracotomy, the hearts were rapidly excised, and the aorta was connected to the isolated perfusion heart system (model iPH-W2, Primetech Co., Japan) using a cannula.…”
Section: Methodsmentioning
confidence: 99%
“…
reports of original investigations 595 CAN J ANESTH 55: 9 www.cja-jca.org September, 2008 Purpose: Propofol exerts cardioprotective effects, but the involved mechanisms remain obscure. The present study examines the cardioprotective effects of propofol and its role in cardiac function, including its effect on K ATP channel opening and the inhibition of GSK-3β activity in ischemia-reperfused hearts.

Methods: Ischemia-reperfusion (I/R) was produced in isolated guinea pig hearts by stopping coronary perfusion for 25 min, followed by reperfusion.

…”
mentioning
confidence: 99%